Exchange Rate Disconnect in General Equilibrium - Itskhoki, Oleg; Mukhin, Dmitry (Journal of Political Economy, 2021)
We propose a dynamic general equilibrium model of exchange rate determination that accounts for all major exchange rate puzzles, including Meese-Rogoff, Backus-Smith, purchasing power parity, and uncovered interest rate parity puzzles. We build on a standard international real business cycle model with home bias in consumption, augmented with shocks in the financial market that result in a volatile near-martingale behavior of exchange rates and ensure their empirically relevant comovement with macroeconomic variables, both nominal and real. Combining financial shocks with conventional productivity and monetary shocks allows the model to reproduce the exchange rate disconnect properties without compromising the fit of the business cycle moments.